2017
DOI: 10.11606/rco.v11i29.122331
|View full text |Cite
|
Sign up to set email alerts
|

Fatores determinantes das book-tax differences

Abstract: Este artigo tem por objetivo identificar quais são os fatores institucionais e não institucionais que determinam as book-tax differences (BTD) das companhias abertas brasileiras. A amostra da pesquisa é composta por 124 companhias, com dados disponíveis para o período de 2010 a 2015. Os resultados indicam que a BTD total apresenta relação positiva com as variáveis rentabilidade, liquidez e a BTD defasada. Quando desmembrados os tipos de BTD, a rentabilidade, o crescimento da receita de vendas e a BTD defasada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
1
10
0
3
Order By: Relevance
“…This result corroborates those of previous studies (Costa & Lopes, 2015;Koubaa & Anis, 2015;Fonseca & Costa, 2017). However, the coefficient signal of the variable SIZE became positive and nonsignificant after the adoption of these norms.…”
Section: Results Of the Estimations For Fixed Effectssupporting
confidence: 92%
See 2 more Smart Citations
“…This result corroborates those of previous studies (Costa & Lopes, 2015;Koubaa & Anis, 2015;Fonseca & Costa, 2017). However, the coefficient signal of the variable SIZE became positive and nonsignificant after the adoption of these norms.…”
Section: Results Of the Estimations For Fixed Effectssupporting
confidence: 92%
“…According to Koubaa and Anis (2015) and Fonseca and Costa (2017), the most profitable companies can expand the deductions and tax credits more effectively to benefit from tax exemptions and to reduce the taxable income in an attempt to reduce the taxes to be paid, thus expanding BTD. Costa and Lopes (2015) also found a positive relationship between profitability (ROA) and BTD.…”
Section: Cost Of Equity Calculated By Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in code law countries where there is more conformity between accounting and tax systems, the form prevails over the essence. In these countries, it is possible to observe a stronger connection between accounting standards and tax regulations (Fonseca & Costa, 2017).…”
Section: Eoretical Framework Tax Aggressivenessmentioning
confidence: 99%
“…However, the authors could not reach a conclusion because the models were not significant. Finally, Fonseca and Costa (2017) have examined the institutional and non-institutional determinants of BTD and found that discretionary accruals were not significant to explain BTD.…”
Section: Book-tax Differences Earnings Management and Tax Avoidancementioning
confidence: 99%